Analysis of the Causes of Pending BPJS Health Claims in Outpatient Services at the Occupational Health Hospital of West Java Province - Rachmadi, Egy Muhammad; Suryani, Ade Irma (Greenation Publisher & Yayasan Global Research National, 2025)
The West Java Provincial Occupational Health Hospital is one of the healthcare facilities that has collaborated with BPJS Health. However, problems still occur in the implementation of the National Health Insurance (JKN) policy, especially regarding pending outpatient service claims. This study aims to identify the factors causing pending BPJS Health claims for outpatient services at the West Java Provincial Occupational Health Hospital. The study employed a quantitative descriptive approach with a cross-sectional design. Sampling was carried out using systematic random sampling, determining certain intervals based on population and sample size. Based on data analyzed from October to December 2024, 88 claim files were found to be pending. Contributing factors include inaccurate coding of the main diagnosis and medical action (38.6%), incomplete evidence of therapy (26.2%), administrative documents (18.2%), and supporting examinations (17%).